Mixing-enthalpy modulation on phase transformation in the gradient chemical core/shell high-entropy shape-memory alloys - E-Wen Huang; Tu-Ngoc Lam; Zachary H. Aitken; Mao-Yuan Luo; Nien-En Chiang; Yuh Sun; Jo-Chi Tseng; Ching-Yu Chiang; Wan-Zhen Hsieh; Wen-Jay Lee; Yong-Wei Zhang; Peter K. Liaw; et al. (Materials & Design)
High-entropy alloys (HEAs) are of more chemical inhomogeneity than traditional alloys. How thermal effects perturb entropy and chemical fluctuations is a major scientific issue. In this study, selected benchmark phenomena revealed by in-situ synchrotron X-ray mapping demonstrates how local chemical gradients control temperature-dependent behaviors in HEAs. Specifically, the gradient chemical layers in the core/shell structure play an important role in the thermally-induced phase transformation of Cu15Ni35Ti50-x(HfZr)x high-entropy shape-memory alloys (HESMAs). The dendritic microstructure in Cu15Ni35Ti20(HfZr)30 exhibits the mixing enthalpy-driven pronounced composition inhomogeneity of an Ni-Hf-rich core and Cu-Zr-Ti-rich shell, demonstrated by thermodynamics calculations and second nearest-neighbor modified embedded atom method (2NN MEAM) formalism. The shell acts as an interfacial energy barrier for the stable martensitic transformation that occurred primarily in the effective Ni-Hf-rich core of the Cu15Ni35Ti20(HfZr)30. The temperature-dependent Gibbs-free energy agrees with the Cu movement, which widens the thermally-induced gradient layer of the elemental redistribution. Our findings are conducive to a potential design strategy of tailoring gradient chemical core/shell HEAs for stable high-temperature shape-memory applications.